Herpes encephalitis and herpetic corneal disease. Issue 664 (February 1981) - Webb, A. K.; Levy, I.
Abstract : A case of herpes encephalitis is reported in a patient who had cranial irradiation and high dose steroids for a cerebral neoplasm. Before radiotherapy the patient had had herpetic infections of the skin and eye.